A technical report of laminate veneers a concept that links aesthetics and periodontics - Monteiro, Mabelle Freitas (Hasanuddin University, 2022)
The adhesive technique's development improved the options for the treatment of healthy teeth that were of irregular shape, size, color, or position in the anterior maxilla and mandible. The continued development of dental ceramics offers clinicians many options for creating highly aesthetic and functional porcelain veneers. This report describes an integrated rehabilitation, using cosmetics materials and periodontal plastic surgery, of a young patient who presented irregular shape in anterior maxillary teeth. The treatment purposed improved periodontal anatomy and aesthetics of teeth. This report aims to guide the clinician for the most important parameters determining the long-term success, correct application, and clinical limitations of laminate porcelain veneers to rebuild the patient's smile in a minimally non-invasive manner.